The Electromagnetic Wave Propagation on the Interface between Low and High Loss Dielectrics - Z. E. Eremenko (Advances in Condensed Matter Physics)
The wave propagation on closed curved interface (a rod or ball) between low and high loss dielectrics was studied and compared with well-known wave propagation problem on flat plane interface between low loss and high loss media. We have studied the propagation of a cylindrical wave along a round dielectric rod immersed into a high loss medium and a spherical wave forming by the oscillations in a dielectric ball immersed into a high loss medium as well. These waves have surface character similar to the wave known as the Zenneck surface wave. The distinctive characteristic of such cylindrical or spherical waves: the more loss in high loss medium the greater its surface character. We showed that the wave attenuation is essentially small at enough big dissipative loss in outer medium of dielectric structures.